2021
DOI: 10.1111/jen.12923
|View full text |Cite
|
Sign up to set email alerts
|

A rapid LAMP‐based colorimetric assay with quick DNA extraction for on‐site identification of Drosophila suzukii Matsumura

Abstract: The spotted wing drosophila, Drosophila suzukii Matsumura (Diptera: Drosophilidae), distributes in most soft‐skinned fruit areas in China, is an economically important pest of fresh cherries during Sino‐European trade and is considered a quarantine pest in A2 list by European and Mediterranean Plant Protection Organization. Loop‐mediated isothermal amplification (LAMP) is an accurate, quick and convenient molecular identification method, applied to distinguish D. suzukii from other fruit flies. This method can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Importantly, the results can be visualized with the naked eye without additional devices. When compared with the colorimetric method (Wang et al, 2021), this method is more intuitive and does not need to distinguish colour differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the results can be visualized with the naked eye without additional devices. When compared with the colorimetric method (Wang et al, 2021), this method is more intuitive and does not need to distinguish colour differences.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid DNA extraction strategy for insects is required to enable simple and portable testing. For example, a sterile toothpick method was developed for the quick extraction of DNA from tephritid fruit flies and combined with LAMP, which is more impurity‐tolerant than PCR for DNA detection (Kitano & Takakura, 2020; Wang et al, 2021). Further studies combining isothermal amplification, rapid DNA extraction, and Cas13a‐LFD are needed to facilitate onsite pest detection in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to morphological-based identification are DNA-based tests, which have the potential to improve detection and reduce reliance on morphological training. In fact, a number of polymerase chain reaction (PCR)-based methods have been developed to identify D. suzukii : PCR restriction fragment length polymorphism (PCR-RFLP) (Kim et al 2014), high-resolution melt analysis, high-resolution melt real-time PCR (HRM-RTPCR) (Dhami and Kumarasinghe 2014), quantitative PCR(qPCR) (Renkema et al 2022), and loop-mediated isothermal amplification PCR (LAMP) (Kim et al 2016, Wang et al 2021). Although these approaches differ, each offers the benefits of high sensitivity and accuracy in target DNA detection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the LAMP assay can successfully detect D. suzukii and discriminate D. suzukii from D. melanogaster (Kim et al 2016), as well as more distantly related tephritid flies (Wang et al 2021). For example, tephritid flies of economic importance to the Sino-European cherry trade have been screened to identify and help prevent international movement, including Bactrocera dorsalis (Hendel) and B. correcta (Bezzi) from China, Rhagoletis cerasi (Linnaeus) from Italy, R. pomonella (Walsh) from the United States, and Ceratitis capitata from Iran (Wang et al 2021). However, the ability of the LAMP assay to accurately discriminate between D. suzukii and closely related drosophilids native to the Midwestern United States, especially those that are commonly captured in D. suzukii monitoring traps, has yet to be tested.…”
Section: Introductionmentioning
confidence: 99%